A model of solar radiation management liability - Pfrommer, Tobias (Discussion paper series, 2018)
Solar Radiation Management (SRM) is a set of potential technologies to counteract climate change. Liability regimes are one potential form of governance institution to avoid global externalities caused by the SRM "free-driver" problem. In this paper I examine the incentives structure and welfare consequences of SRM liability regimes. Characteristics specific to SRM impact on the incentives that liability regimes provide via the definition of harm and the liability standard. Consequently, a liability regime is defined as a combination of a definition of harm and a liability standard in the model. Providing several interpretations of these two dimensions adequate for the SRM context, I show that only one combination implements the social optimum. A numerical implementation of the model yields that the free-driver problem is moderate given a metric of mean temperature and extreme given a metric of mean precipitation. Furthermore, the implementation suggests that liability regimes are generally capable of mitigating the free-driver problem substantially and that the choice of the definition of harm is more consequential than the choice of the liability standard. Keywords: Solar Radiation Management, Liability Regimes, Externalities, Climate Engineering, Free-Driver Scenario. JEL Codes: Q53, Q54, K13
Keywords: Graue Literatur